Occupational Accidents among Fishermen in Manado, North Sulawesi - Fitri M. Suhartoyo; Oksfriani J. Sumampouw; Novie H. Rampengan (e-CliniC, 2022)
Abstract: The International Labor Organization (ILO) noted that at global level more than 2.78 million people die per year due to occupational accidents or work-related diseases. In addition, there are approximately 374 million injuries and illnesses resulting from non-fatal occupational accidents each year. The Food and Agriculture Organization (FAO) in "The State of World Fisheries and Aquaculture" reported, as many as 24,000 fishermen per year died at sea during fishing activities. This study aimed to identify the prevalence of occupational accidents among fishermen in Manado City, North Sulawesi. This was a quantitative and analytical survey study using the cross-sectional design. This study was conducted at the Coastal Fishing Port Manado City, North Sulawesi and respondents were 264 fishermen. The instrument used in this study was a questionnaire that had been tested for validity and reliability. The results showed the prevalence of occupational accident was 70.8%. The description of the respondentsâ€™ occupational accidents showed that the most common experienced accident was injury as many as 47.7%, and the most injured body part was the hand as many as 37.1%. In conclusion, the prevalence of occupational accident among fishermen in Manado, North Sulawesi is still high.Keywords: work accident; fishermenÂ Abstrak: International Labour Organization (ILO) mencatat, di tingkat global lebih dari 2,78 juta orang meninggal per tahun akibat kecelakaan kerja atau penyakit terkait pekerjaan. Selain itu, ada sekitar 374 juta cedera dan penyakit akibat kecelakaan kerja non-fatal setiap tahun. Food and Agriculture Organization (FAO) dalam "The State of World Fisheries and Aquaculture" melaporkan, sebanyak 24.000 nelayan per tahun meninggal dunia di laut pada saat kegiatan penangkapan ikan. Penelitian ini bertujuan untuk mengidentifikasi prevalensi kecelakaan kerja pada nelayan di Kota Manado Sulawesi Utara. Jenis penelitian ialah kuantitatif dengan rancangan penelitian survei analitik, menggunakan desain potong lintang. Penelitian ini dilakukan di Pelabuhan Perikanan Pantai (PPP) Kota Manado Sulawesi Utara. Responden penelitian berjumlah 264 nelayan. Instrumen penelitian berupa angket yang telah diuji validitas dan reliabilitasnya. Hasil penelitian mendapatkan bahwa prevalensi kecelakaan kerja sebesar 70,8%. Gambaran kecelakaan kerja responden menunjukkan bahwa jenis kecelakaan yang dialami paling banyak ialah mengalami luka sebesar 47,7%, dan bagian tubuh yang mengalami cedera paling banyak ialah pada bagian tangan sebesar 37,1%. Simpulan penelitian ini ialah prevalensi kecelakaan kerja pada nelayan di Kota Manado, Sulawesi Utara masih tinggi.Kata kunci: kecelakaan kerja; nelayan